Climate ethics and climate justice in the context of the Global South - Akkuş, Aygül (Cappadocia Journal of Area Studies, 2021)
The fact that those most affected by the climate crisis are those who are least affected by it forms the basis of climate justice. This study examines climate justice and climate ethics policies and practices by addressing the Americas, Asia and Africa continents. Considering that climate justice cannot be considered separately from climate ethics and that this is an ethical issue at the same time, it is aimed to deal with climate ethics and climate justice debates based on environmental ethics understandings. As a method, literature review was made, climate justice searches and examples were evaluated based on the conceptual framework and ethical foundations. As a result, if the moral interest turns towards ecocentrism, who is responsible for the climate crisis, which species, which classes and which living and non-living things in the ecosystem are most affected by this crisis, who and/or what should be protected, and the rights of future generations should be taken into consideration. Questions such as who will undertake the protection mission gain weight. With this holistic perspective to be created, it will be possible to seek a solution to the climate crisis in which responsibilities for the entire ecosystem are shared, ethical values ​​come to the fore, and the concepts of fairness and justice find their place for all living and non-living beings. The ethical understanding to be formed within the framework of the answers to these questions constitutes the basis of both climate ethics and climate justice. Therefore, it seems inevitable that with the climate ethics approach to be adopted within the framework of these questions, it is inevitable to establish an understanding of global climate justice that includes living and non-living things in the field of moral interest, interspecies, international, inter-class, intra-generational and intergenerational global climate justice.